The Impact of Hypertension on Patients with Acute Coronary Syndromes - Claudio Picariello; Chiara Lazzeri; Paola Attanà; Marco Chiostri; Gian Franco Gensini; Serafina Valente (International Journal of Hypertension)
Arterial chronic hypertension (HTN) is a well-known cardiovascular risk factor for development of atherosclerosis. In order to explain the relation between HTN and acute coronary syndromes the following factors should be considered: (1) risk factors are shared by the diseases, such as genetic risk, insulin resistance, sympathetic hyperactivity, and vasoactive substances (i.e., angiotensin II); (2) hypertension is associated with the development of atherosclerosis (which in turn contributes to progression of myocardial infarction). From all the registries and the data available up to now, hypertensive patients with ACS are more likely to be older, female, of nonwhite ethnicity, and having a higher prevalence of comorbidities. Data on the prognostic role of a preexisting hypertensive state in ACS patients are so far contrasting. The aim of the present paper is to focus on hypertensive patients with ACS, in order to better elucidate whether these patients are at higher risk and deserve a tailored approach for management and followup.